Beam dynamics optimisation of an X-band Linac driven soft X-ray FEL - Bartolini, R (2011)
Several new light source projects aim at producing X-ray photons with high repetition rate (1 kHz or above). Cost and size considerations have recently stirred new interest in solutions based on X-band RF systems. We developed a conceptual design for a soft X-ray FEL driven by X-band structures operating at high repetition rate and we present here the results of the start-to-end simulations from the gun to the end of the undulators and the corresponding optimisation of the FEL performance at 1 keV photon energy. © 2011 Elsevier B.V. All rights reserved.